Nairang-i ḵẖayāl : Iqbāl nambar - Ḥasan, Badruddīn; Ḥasan, Muḥammad Yūsuf (SAMP early 20th-century Indian books project ;, 1932)
Contributed articles on the life and works of Sir Muhammad Iqbal, 1877-1938, Urdu poet.